Gamma Delta T-lymphocytes in Hepatitis C and Chronic Liver Disease - Rajoriya, Neil; Fergusson, Joannah Ruth; Leithead, Joanna A.; Klenerman, Paul (Frontiers in Immunology, 2014)
Discovered thirty years ago, gamma delta (γδ) T-lymphocytes remain an intriguing and enigmatic T-cell subset. Although in humans they comprise a small fraction of the total circulating T-lymphocyte pool, they represent an important T-cell subset in tissues such as the liver, with roles bridging the innate and adaptive immune systems. The associations of γδ T-lymphocytes with chronic liver disease have been explored - however there remain conflicting data as to whether these T-cells are pathogenic or protective. In patients with some forms of liver disease, their expansion in the periphery and especially in the liver may indeed help pathogen clearance, while in other conditions their presence may, in contrast, contribute to disease progression. Gamma-delta T cells can also express CD161, a C-type lectin, and such cells have been found to be involved in the pathogenesis of inflammatory disease. CD161+ T-cells of diverse subsets are known to be enriched in the livers of patients with chronic hepatitis C. This article serves to provide a review of the γδ T-cell population and its role in chronic liver disease, and also to explore a potential role of the CD161+ γδ T-cells in liver disease.